Answer:
3
Step-by-step explanation:
It should be 3 because when you look at it divide them all and each one gives you 3. If it's not then sorry.
Answer:
.
Step-by-step explanation:
We have been given an equation
. We are supposed to solve our given equation step by step.
Step 1: Use the distributive property.
![3\cdot 2x+3\cdot 6-4x=2\cdot 5x-2\cdot 2+6](https://tex.z-dn.net/?f=3%5Ccdot%202x%2B3%5Ccdot%206-4x%3D2%5Ccdot%205x-2%5Ccdot%202%2B6)
![6x+18-4x=10x-4+6](https://tex.z-dn.net/?f=6x%2B18-4x%3D10x-4%2B6)
Step 2: Combine like terms.
![6x-4x+18=10x-4+6](https://tex.z-dn.net/?f=6x-4x%2B18%3D10x-4%2B6)
![2x+18=10x+2](https://tex.z-dn.net/?f=2x%2B18%3D10x%2B2)
Step 3: Use subtraction property of equality:
![2x-2x+18-2=10x-2x+2-2](https://tex.z-dn.net/?f=2x-2x%2B18-2%3D10x-2x%2B2-2)
![16=8x](https://tex.z-dn.net/?f=16%3D8x)
Step 4: Use the division property of equality:
![\frac{16}{8}=\frac{8x}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B16%7D%7B8%7D%3D%5Cfrac%7B8x%7D%7B8%7D)
![2=x](https://tex.z-dn.net/?f=2%3Dx)
Therefore, the solution of our given equation is
.
-12 n - 24 = -12 (n+2)
-12 (n+2) is the answer
Answer:
<em>The monthly payment is $450.71</em>
Step-by-step explanation:
<u>Financial Computing
</u>
Given the loan amount A, the loan term t, and the APR (annual percentage rate), the montly payment is computed as
![\displaystyle P=\frac{A}{f}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20P%3D%5Cfrac%7BA%7D%7Bf%7D)
where f is
![\displaystyle f=\frac{1-(1+i)^{-n}}{i}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%3D%5Cfrac%7B1-%281%2Bi%29%5E%7B-n%7D%7D%7Bi%7D)
The provided data is
![\displaystyle A=24,000](https://tex.z-dn.net/?f=%5Cdisplaystyle%20A%3D24%2C000)
![\displaystyle r=4.8\%](https://tex.z-dn.net/?f=%5Cdisplaystyle%20r%3D4.8%5C%25)
![\displaystyle t=5\ years](https://tex.z-dn.net/?f=%5Cdisplaystyle%20t%3D5%5C%20years)
Since the payments will be made monthly, the values of n and i are:
![\displaystyle i=\frac{4.8}{100\times12}=0.004](https://tex.z-dn.net/?f=%5Cdisplaystyle%20i%3D%5Cfrac%7B4.8%7D%7B100%5Ctimes12%7D%3D0.004)
![\displaystyle n=5\times12=60\ months](https://tex.z-dn.net/?f=%5Cdisplaystyle%20n%3D5%5Ctimes12%3D60%5C%20months)
Calculating f:
![\displaystyle f=\frac{1-(1+i)^{-n}}{i}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%3D%5Cfrac%7B1-%281%2Bi%29%5E%7B-n%7D%7D%7Bi%7D)
![\displaystyle f=\frac{1-(1+0.004)^{-60}}{0.004}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%3D%5Cfrac%7B1-%281%2B0.004%29%5E%7B-60%7D%7D%7B0.004%7D)
![\displaystyle f=53.25](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%3D53.25)
Now for the payments:
![\displaystyle P=\frac{24.000}{53.25}=450.71](https://tex.z-dn.net/?f=%5Cdisplaystyle%20P%3D%5Cfrac%7B24.000%7D%7B53.25%7D%3D450.71)
![\boxed{\displaystyle P=\$450.71}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cdisplaystyle%20P%3D%5C%24450.71%7D)
Answer:
Compare the given equation of the circle (x - 1)² + (y -2)² = 2²
with standard form of circle: (x - h)² + (y - k)² = r²
Here, (h, k) is the center of the circle
and r is the radius of the circle.
Thus, The center of the circle is: (1, 2)
Also, for finding the point of intersections of (x - 1)² + (y -2)² = 2² and y = 2x + 2,
Substitute the value of y from equation of line in the equation of circle.
(x - 1)² + (2x + 2 - 2)² = 2²
⇒ (x - 1)² + (2x)² = 2²
⇒ x² + 1 - 2x + 4x² = 4
⇒ 5x² - 2x - 3 = 0
Applying Middle term splitting method
5x² - 5x + 3x - 3 = 0
⇒ 5x(x - 1) + 3(x - 1) = 0
⇒ (5x + 3)(x - 1) = 0
⇒ x =
and x = 1
Thus, we get coordinates:
and (1, 4)